Beyond Isolated Optimization: A Holistic Review Across the Pre-Mid Post-Treatment Chain for Hard Carbon in Sodium-Ion Battery - Geng, Qingxuan; Zhang, Yonghui; Xie, Dongxu; Hao, Chenhui; Guo, Liping; Zhang, Jiwei; Chu, Paul K.; Li, Qingwei (Nano-Micro Letters, 2026)
Commercialization of sodium-ion batteries depends on the advancement of high-performance hard carbon (HC) anodes. Their complex microstructure, composed of graphitic nanodomains, nanopores, and defects, fundamentally governs sodium storage. However, most design of HC is hampered by a fragmented research approach focusing on single-point optimization. Isolated improvements in the precursor selection, pyrolysis, or post-treatment often produce unsatisfactory results due to overlooked synergistic effects across the entire fabrication chain. This review addresses this challenge by proposing a holistic, full-process engineering perspective. We first clarify how the core structural features of HC collectively determine the storage mechanism. We then systematically examine the roles of pretreatment, mid-process control, and post-treatment in microstructural manipulation. We also critically assess and comparatively evaluate these strategies by identifying their respective strengths, shortcomings, and interdependencies. Our analysis emphasizes that treatments at one stage precondition outcomes at another, highlighting key coupling points for synergistic optimization. How to coordinate these strategies in industrial production to obtain batch performance stable HC has also been discussed. Finally, we put forward future research directions, focusing on establishing quantitative microstructure–property relationships through advanced characterization and modeling, developing cross-stage co-design strategies, and evaluating process scalability and sustainability. This review aims to guide the transition of HC anode development from exploratory confusion toward rational, predictive engineering. Highlights: 1 Proposes a holistic “Pre-Mid-Post” full-process engineering mode to go beyond fragmented single-point optimization of hard carbon anodes 2 Elucidates the synergistic and contradictory interplay among graphitic domains, nanopores, and defects in determining the Na⁺ storage properties 3 Future design necessitates cross-stage co-optimization and quantitative microstructure–performance relationships for rational HC engineering